Efficacy and safety of fumaric acid esters in young patients aged 10–17 years with moderate‐to‐severe plaque psoriasis: a randomized, double‐blinded, placebo‐controlled trial. (22nd February 2021) - Hamm, H.; Wilsmann‐Theis, D.; Tsianakas, A.; Gambichler, T.; Taipale, K.; Lauterbach, J.; Freudensprung, U.; Makepeace, C.; ,
Summary: Background: Apart from biologics, no systemic drugs are approved in Europe for children with moderate‐to‐severe psoriasis. Retrospective observational studies have shown promising results for fumaric acid esters (FAE) in this setting. Objectives: To show superiority of FAE over placebo in terms of treatment response after 20 weeks in children and adolescents aged 10–17 years. Methods: In a multicentre, randomized, double‐blind, placebo‐controlled phase IIIb study, patients aged 10–17 years with moderate‐to‐severe plaque psoriasis requiring systemic therapy were randomized 2 : 1 to receive FAE ( n  = 91) or placebo ( n  = 43) over 20 weeks, followed by an open‐label FAE treatment phase. The coprimary endpoints were ≥ 75% improvement in Psoriasis Area and Severity Index (PASI 75) and Physician's Global Assessment (PGA) score of 0 or 1 (clear or almost clear) at week 20. The study was registered with EudraCT number 2012‐000035‐82. Results: At week 20, 55% [95% confidence interval (CI) 0·44–0·65] of FAE‐treated patients achieved a PASI 75 response vs. 19% (95% CI 0·08–0·33) in the placebo group (absolute difference 36%, 95% CI 0·20–0·53; P  < 0·001). In total, 42% (95% CI 0·32–0·53) in the FAE group vs. 7% (95% CI 0·01–0·19) in the placebo group achieved a PGA score of 0 or 1 at week 20 (absolute difference 35%, 95% CI 0·21–0·49; P  < 0·001). During the double‐blind period, drug‐related adverse events occurred more frequently in patients receiving FAE compared with placebo (76% vs. 47%). Gastrointestinal disorders were the most common adverse events. Conclusions: FAE administered over a period of 20 weeks demonstrated a better response than placebo; the difference was statistically significant and clinically meaningful. Application up to 40 weeks was generally well tolerated. However, further studies are required. Abstract : What is already known about this topic? Fumaric acid esters (FAE) are recommended by the 2015 European evidence‐based S3‐guidelines on psoriasis treatment as a systemic option for moderate‐to‐severe plaque psoriasis in adults. FAE are effective in adult patients with psoriasis and have a favourable long‐term safety profile. What does this study add? This is the first randomized controlled trial conducted with FAE in children and adolescents aged 10–17 years with moderate‐to‐severe plaque psoriasis requiring systemic treatment. FAE are effective in children and adolescents. Linked Comment:  B. Volc‐Platzer. Br J Dermatol 2021; 185 :5–6 .